2009
DOI: 10.1164/rccm.200901-0156oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneity of Lung Parenchyma during the Open Lung Strategy

Abstract: Alveolar recruitment is not protective against hyperinflation of the baby lung because lung parenchyma is inhomogeneous during ventilation with the open lung strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 45 publications
4
75
2
3
Order By: Relevance
“…Third, although a decrease in cardiac output could have per se decreased shunt and improved oxygenation [37], we found that cardiac output remained unchanged. Fourth, the slight but significant increase of E L with the higher PEEP strategy may be explained assuming that in these patients the increase of PEEP shifted tidal ventilation close to upper inflection point of the pulmonary volume-pressure curve [39][40][41] as also supported by recent evidence suggesting that "regional elastance" of lung tissue previously collapsed and re-expanded by applied pressure is higher than the elastance of the normally patent lung regions [42].…”
Section: Discussionmentioning
confidence: 78%
“…Third, although a decrease in cardiac output could have per se decreased shunt and improved oxygenation [37], we found that cardiac output remained unchanged. Fourth, the slight but significant increase of E L with the higher PEEP strategy may be explained assuming that in these patients the increase of PEEP shifted tidal ventilation close to upper inflection point of the pulmonary volume-pressure curve [39][40][41] as also supported by recent evidence suggesting that "regional elastance" of lung tissue previously collapsed and re-expanded by applied pressure is higher than the elastance of the normally patent lung regions [42].…”
Section: Discussionmentioning
confidence: 78%
“…FRC [13]. Both lung stress and strain have been recently investigated as possible parameters to quantify the mechanical insult commencing the entire cascade of VILI, whether is deemed to be either an inflammatory or a pure mechanical process (or a combination of the two) [14,17]. Considering V T as the most commonly employed parameter in experimental VILI, we did not observe any correlation between the time to achieve preterminal lung injury and the V T /kg body weight applied, while a strict and exponential correlation was observed between the duration of mechanical ventilation and lung strain.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the strict and exponential correlation between the time to achieve preterminal lung injury and the lung strain or the weighted lung strain applied may also indicate a critical threshold suggesting two possible different mechanisms for the development of VILI: (1) development of VILI directly related to the excessive global stress and strain applied (above a value of weighted lung strain of 2.0), and (2) a less rapid time-course probably associated with different mechanisms other than the pure application of an excessive global stress and strain (below a value of weighted lung strain of 1.5), such as a regional dishomogeneity in the stress/strain distribution [17], intratidal alveolar opening and closing [5,6], regional hypocapnia [25] and regional areas of stress/strain amplification [26]. Such observations may have important consequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of one experimental study challenged this hypothesis (57). Further, in a model of mechanically ventilated pigs, other investigators found that alveolar recruitment was not protective against alveolar hyperinflation, because recruited lung tissue has mechanical properties that are different from those of the surrounding collapsed or consolidated lung (58). The significance of this work was well discussed in a related commentary (59).…”
Section: Treatment Of Acute Lung Injury: Experimental Studiesmentioning
confidence: 94%